Dietary fat saturation produces lipid modifications in peritoneal macrophages of mouse - Oliveros, Liliana Beatriz (2003)
We investigated the effects of a saturated fat diet on mice lipid metabolism in resident peritoneal macrophages. Male C57BL/6 mice were weaned at 21 days of age and assigned to either the experimental diet, containing coconut oil (COCO diet), or the control diet, containing soybean oil as fat source. Fat content of each diet was 15% (w/w). Mice were fed for 6 weeks until sacrifice. In plasma of mice fed the COCO diet, the concentration of triglyceride, total cholesterol, HLD- and (LDL+VLDL)-cholesterol, and thiobarbituric acid-reactive substances (TBARS) increased, without changes in phospholipid concentration, compared with the controls. In macrophages of COCO-fed mice, the concentration of total (TC), free and esterified cholesterol, triglyceride, phospholipid (P) and TBARS increased, while the TC/P ratio did not change. The phospholipid compositions showed an increase of phosphatidylcholine and phosphatidylserine + phosphadytilinositol, a decrease of phosphatidylethanolamine, and no change in phosphatidylglycerol. 3H2O incorporation into triglyceride and phospholipid fractions of macrophages increased, while its incorporation into free cholesterol decreased. Incorporation of [3H]cholesterol into macrophages of COCO-fed mice and the fraction of [3H]cholesterol ester increased. COCO diet produced an increase in myrystic, palmitic and palmitoleic acids proportion, a decrease in linoleic and arachidonic acids and no changes in stearic and oleic acids, compared with the control. Also, a higher relative percentage of saturated fatty acid and a decrease in unsaturation index (p <0.001) were observed in macrophages of COCO-fed mice. These results indicate that the COCO-diet, high in saturated fatty acids, alters the lipid metabolism and fatty acid composition of macrophages and produces a significant degree of oxidative stress.